SCHOOL ENVIRONMENT AS A SUBJECT OF DESIGN OF EDUCATIONAL SPACE IN SCHOOL (Pedagogy of Higher and Secondary Education, 2022)
The directions of innovative educational processes in the school at two levels are identified: as local innovations in the traditional education system that do not change the educational environment of the school and as the introduction of holistic educational systems that promote an innovative school environment in design. Developmental educational systems that form a personality-oriented school environment are analyzed. The conditions of effective functioning of the age educational space are determined. Features of anthropologically oriented schools are described. Models of the innovative educational environment of schools are proposed, where the priority areas are humanization, greening, and integration.
Keywords: school environment; design; educational space